2001
DOI: 10.4049/jimmunol.167.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Common γ-Chain Is an Indispensable Subunit of the IL-21 Receptor Complex

Abstract: The common gamma-chain (gamma(c)) is an indispensable subunit of the functional receptor complexes for IL-4, IL-7, IL-9, and IL-15 as well as IL-2. Here we show that the gamma(c) is also shared with the IL-21R complex. Although IL-21 binds to the IL-21R expressed on gamma(c)-deficient ED40515(-) cells, IL-21 is unable to transduce any intracytoplasmic signals. However, in EDgamma-16 cells, a gamma(c)-transfected ED40515(-) cell line, IL-21 binds to the IL-21R and can activate Janus kinase (JAK)1, JAK3, STAT1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
400
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 487 publications
(423 citation statements)
references
References 30 publications
15
400
2
3
Order By: Relevance
“…A recent study shows that T-bet is required for IFN-␥ production in CD4 and NK cells, but not in CD8 T cells (40). T-bet can also stimulate indirectly its own gene expression by inducing IFN-␥, which in turn activates T-bet gene expression (41,42 (2,43). In addition, the IL-2/IL-15R␤ subunit that is essential for the proliferation of NK and T cells is also closely related to IL-21R.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study shows that T-bet is required for IFN-␥ production in CD4 and NK cells, but not in CD8 T cells (40). T-bet can also stimulate indirectly its own gene expression by inducing IFN-␥, which in turn activates T-bet gene expression (41,42 (2,43). In addition, the IL-2/IL-15R␤ subunit that is essential for the proliferation of NK and T cells is also closely related to IL-21R.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Asao et al (2) suggested that IL-21 stimulation lead to the activation of JAK1 and JAK3 in a ␥ c -transfected T cell line. We analyzed whether JAK1 or JAK3 was activated by IL-21 also in NK and T cells.…”
Section: Il-21 Induces Jak1 and Jak3 Tyrosine Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial limitations of the SCID and NOD-SCID mice for the implantation and long term survival of human normal and neoplastic tissues have now been overcome by the generation of a new generation of NOD-SCID mouse with a null mutation of the IL-2 common γ chain receptor [130][131][132]. These NOD-SCID IL2Rγ null mice are called NOG mice, and the IL-2R mutation results in a defect of the high affinity receptors for IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21 that blocks the development of NK cells and further impairs innate immunity [130,133].…”
Section: Mouse/human Xenograft Models To Study In Vivo Dynamic Interamentioning
confidence: 99%
“…The IL-21 receptor complex consists of the common cytokine receptor g chain and IL-21R. 7,8 A recent study of mice lacking IL-21R demonstrated that IL-21 could facilitate the transition from NK cellmediated innate immunity to T cell-mediated adaptive immunity. 9 However, contradictory results were also reported; IL-21 is secreted from Th2 cells and inhibits the development of interferon-g (IFN-g)-producing Th1 cells.…”
mentioning
confidence: 99%